Auditory cortex activity measured using functional near-infrared spectroscopy (fNIRS) appears to be susceptible to masking by cortical blood stealing - Steinmetzger, Kurt; Shen, Zhengzheng; Riedel, Helmut; Rupp, André (Hearing research, 2020)
To validate the use of functional near-infrared spectroscopy (fNIRS) in auditory perception experiments, combined fNIRS and electroencephalography (EEG) data were obtained from normal-hearing subjects passively listening to speech-like stimuli without linguistic content. The fNIRS oxy-haemoglobin (HbO) results were found to be inconsistent with the deoxy-haemoglobin (HbR) and EEG data, as they were dominated by increasingly more negative responses along a diagonal axis running in posterior-superior to anterior-inferior direction. This large-scale bilateral gradient in the HbO data masked the right-lateralised neural activity in the auditory cortex that was clearly evident in the HbR data and EEG source reconstructions and is most likely due to cerebral blood stealing. When the subjects were subsequently split into subgroups with more positive or more negative HbO responses in the right auditory cortex, the former group surprisingly showed smaller event-related potentials and increased EEG alpha power, indicating reduced attention and vigilance. These findings thus suggest that positive HbO responses in the auditory cortex may not necessarily be a favourable result when investigating auditory perception using fNIRS. More generally, the results show that the interpretation of fNIRS HbO signals can be misleading and demonstrate the benefits of combined fNIRS-EEG analyses.